Study on In-Doped CdMgTe Crystals Grown by a Modified Vertical Bridgman Method Using the ACRT Technique - Yu, Pengfei (Materials (Basel), 2019)
Cadmium–magnesium–telluride (CdMgTe) crystal was regarded as a potential semiconductor material. In this paper, an indium-doped Cd(0.95)Mg(0.05)Te ingot with 30 mm diameter and 120 mm length grown by a modified Bridgman method with excess Te condition was developed for room temperature gamma-ray detection. Characterizations revealed that the as-grown Cd(0.95)Mg(0.05)Te crystals had a cubic zinc-blende structure and additionally Te-rich second phase existed in the crystals. From the tip to tail of the ingot, the density of Te inclusions was about 10(3)–10(5) cm(−2). The crystals had a suitable band-gap range from 1.52–1.54 eV. Both infrared (IR) transmittance and resistivity were relatively low. Photoluminescence measurement indicated that the ingot had more defects. Fortunately, after annealing, IR transmittance and the resistivity were significantly enhanced due to the elimination of Te inclusions. CdMgTe crystal after annealing showed a good crystal quality. The energy resolutions of the detector for (241)Am and (137)Cs gamma-ray were 12.7% and 8.6%, respectively. The mobility-lifetime product for electron was 1.66 × 10(−3) cm(2)/V. Thus, this material could be used for room temperature radiation detectors.